2016
DOI: 10.1080/0284186x.2016.1213415
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness for side effects and bother in symptomatic men after radical prostatectomy in a prospective, non-randomized trial, LAPPRO

Abstract: on behalf of the LAPPRO steering committee (2016) Preparedness for side effects and bother in symptomatic men after radical prostatectomy in a prospective, non-randomized trial, LAPPRO, Acta Oncologica, 55:12, 1467-1476, DOI: 10.1080 Background: Many clinicians believe that preparedness before surgery for possible post-surgery side effects reduces the level of bother experienced from urinary incontinence and decreased sexual health after surgery. There are no published studies evaluating this belief. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Of the 18 articles included, (5)(6)(7)(8)11,12,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) 17 were found in the electronic databases and one in the references of the selected studies. In the reference lists of the excluded reviews, no study was found that complied with the inclusion criteria set.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 18 articles included, (5)(6)(7)(8)11,12,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) 17 were found in the electronic databases and one in the references of the selected studies. In the reference lists of the excluded reviews, no study was found that complied with the inclusion criteria set.…”
Section: Resultsmentioning
confidence: 99%
“…In the reference lists of the excluded reviews, no study was found that complied with the inclusion criteria set. As for the language of the articles, 16 were published in English, (5,6,8,11,12,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) one in Spanish (7) and one in Portuguese. (23) As for the country where the study was developed, three were developed in Spain, followed by the United States, United Kingdom, Italy, Australia and China, with two studies each, and Brazil, Denmark, Sweden, Norway and The Netherlands, with one study in each country.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Эти данные свидетельствуют о необходимости проведения реабилитационных мероприятий у этой категории больных, что согласуется с мнением ряда авторов [19,20]. С одной стороны, они связаны с оказанием психологической поддержки, а иногда и психиатрической помощи, и имеются публикации об эффективности этих мероприятий [21][22][23], а с другой -с мероприятиями по восстановлению возможности половой жизни. Из больных с развившейся после операции ЭД 34,2% хотели бы улучшить сексуальную функцию [6].…”
Section: обсуждение результатовunclassified